2022
DOI: 10.1200/jco.2022.40.16_suppl.e16147
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of camrelizumab and apatinib combination therapy versus apatinib only in treatment of advanced hepatocellular carcinoma: A meta-analysis.

Abstract: e16147 Background: Recent studies have assessed the efficacy of some therapeutics in advanced hepatocellular carcinoma. Our aim is to perform a meta-analysis to compare the efficacy of Camrelizumab and Apatinib combination therapy versus Apatinib only in treatment of advanced hepatocellular carcinoma. Methods: We searched PubMed, WOS, Embase and Scopus databases. Inclusion criteria were clinical trials and cohort studies that evaluated the efficacy of Camrelizumab and Apatinib combination therapy or Apatinib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…First, patient eligibility is restricted with only those meeting the current inclusion criteria (limited to cases with a Child–Pugh A score) being considered, primarily because of the occurrence of severe immune-related adverse events resulting from the long half-life and off-target effects of mAbs. , Second, the high cost of treatment is rooted in the complexity of mAb production. , Consequently, recent clinical studies have shown a growing inclination toward the incorporation of more cost-effective small-molecule inhibitors. Thus, the combination of small-molecule TKIs with antiangiogenesis properties, such as apatinib (Apa), regorafenib, or lenvatinib, with mAb targeting of PD-1/PD-L1, has displayed enhanced antitumor efficacy in clinical trials for treating advanced HCC. Certainly, the contrasting physicochemical properties inherent to these two types of drugs produce distinct pharmacokinetic profiles. Consequently, when employed concurrently, this divergence in their pharmacokinetics may result in a notable delay in achieving the desired therapeutic effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…First, patient eligibility is restricted with only those meeting the current inclusion criteria (limited to cases with a Child–Pugh A score) being considered, primarily because of the occurrence of severe immune-related adverse events resulting from the long half-life and off-target effects of mAbs. , Second, the high cost of treatment is rooted in the complexity of mAb production. , Consequently, recent clinical studies have shown a growing inclination toward the incorporation of more cost-effective small-molecule inhibitors. Thus, the combination of small-molecule TKIs with antiangiogenesis properties, such as apatinib (Apa), regorafenib, or lenvatinib, with mAb targeting of PD-1/PD-L1, has displayed enhanced antitumor efficacy in clinical trials for treating advanced HCC. Certainly, the contrasting physicochemical properties inherent to these two types of drugs produce distinct pharmacokinetic profiles. Consequently, when employed concurrently, this divergence in their pharmacokinetics may result in a notable delay in achieving the desired therapeutic effectiveness.…”
Section: Introductionmentioning
confidence: 99%